2020
DOI: 10.1021/acsapm.9b01076
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Tolerant PET-RAFT Facilitated 3D Printing of Polymeric Materials under Visible LEDs

Abstract: The photopolymerization-based 3D printing process is typically conducted by using free radical polymerization, which leads to fabrication of immutable materials. An alternative 3D printing of polymeric materials by using trithiocarbonate (TTC) reversible addition–fragmentation chain transfer (RAFT) agents has always been a challenge for material and polymer scientists. Herein we report 3D printing of RAFT-based formulations that can be conducted fully open to air using a standard digital light processing (DLP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 70 publications
1
117
0
Order By: Relevance
“…In addition to these applications, oxygen tolerance has also significantly simplified the reaction setup for performing surface-initiated polymerizations, [105,106] and for the translation of RAFT into 3D printing. [107,108] Complimenting the observed improvements in interlayer bonding, the application of RAFT holds the promise of finer control over the nano/microstructure of printed materials and the programming of new functions and stimuli-responsivity.…”
Section: Oxygen-tolerant Raftmentioning
confidence: 99%
“…In addition to these applications, oxygen tolerance has also significantly simplified the reaction setup for performing surface-initiated polymerizations, [105,106] and for the translation of RAFT into 3D printing. [107,108] Complimenting the observed improvements in interlayer bonding, the application of RAFT holds the promise of finer control over the nano/microstructure of printed materials and the programming of new functions and stimuli-responsivity.…”
Section: Oxygen-tolerant Raftmentioning
confidence: 99%
“…[EY]: [TEA], which was able to be printed under both blue (λmax = 483 nm, 4.16 mW/cm 2 ) and green (λmax = 532 nm, 0.48 mW/cm 2 ) lights 22 . This resin was slower to polymerize compared to conventional free radical polymerization (FRP) equivalents and produced objects with a maximum build speed of 1354 µm/hr under green light.…”
Section: D-raft Printing Resin Formulation and Propertiesmentioning
confidence: 99%
“…Within a network a symmetric RAFT agent will provide intranetwork growth in size and mass by expanding the chains between crosslinking points, whereas an asymmetric RAFT agent will also cause network-wide growth but only at the chain ends, making it more suitable for surface growth and functionalization 20 . Previously our group has demonstrated 3D printing techniques based on photo-RAFT polymerization under various visible wavelengths (405nm, 483nm and 532nm) ; both via an iniferter mechanism under an inert atmosphere 21 , and via PET-RAFT in open air 22 . In both studies we demonstrated the facile surface modification that could be performed on the samples after printing with a range of different monomers; pyrene methyl methacrylate (PyMA) for a light response, N-isopropylacrylamide (NIPAM) for temperature response, and butyl acrylate (BA) to modify the surface hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations